miR-143 Regulates Lysosomal Enzyme Transport across the Blood-Brain Barrier and Transforms CNS Treatment for Mucopolysaccharidosis Type I - Lin, Yi (Mol Ther, 2020)
During brain maturation, cation-independent mannose-6-phosphate receptor (CI-MPR), a key transporter for lysosomal hydrolases, decreases significantly on the blood-brain barrier (BBB). Such a phenomenon leads to poor brain penetration of therapeutic enzymes and subsequent failure in reversing neurological complications in patients with neuropathic lysosomal storage diseases (nLSDs), such as Hurler syndrome (severe form of mucopolysaccharidosis type I [MPS I]). In this study, we discover that upregulation of microRNA-143 (miR-143) contributes to the decline of CI-MPR on the BBB during development. Gain- and loss-of-function studies showed that miR-143 inhibits CI-MPR expression and its transport function in human endothelial cells in vitro. Genetic removal of miR-143 in MPS I mice enhances CI-MPR expression and improves enzyme transport across the BBB, leading to brain metabolic correction, pathology normalization, and correction of neurological functional deficits 5 months after peripheral protein delivery at clinically relevant levels that derived from erythroid/megakaryocytic cells via hematopoietic stem cell-mediated gene therapy, when otherwise no improvement was observed in MPS I mice at a parallel setting. These studies not only uncover a novel role of miR-143 as an important modulator for the developmental decline of CI-MPR on the BBB, but they also demonstrate the functional significance of depleting miR-143 for “rescuing” BBB-anchored CI-MPR on advancing CNS treatment for nLSDs.